IMPLIKATUR PERCAKAPAN DAN PELANGGARAN PRINSIP KERJA SAMA DALAM DIALOG HUMOR - Ardiansyah, Roely (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
People express their purpose or intention of saying in different ways, so that, listener or reader could or could not probably understand the meaning of the expression. It can probably be caused by the implicitness of the meaning of sentences being used. Even more happening to the dialogue of humor. Therefore, humor can cause laughter to the listener and has the properties contain unexpected surprises, breaking taboos, thereby intentionally causing ambiguity, when the communication process takes place. It thus called conversational implicatures and violation of the cooperative principle. Following the findings of the conversational humor, namely (1) the forms implicatures found a conversational implicatures in the form of questions and statements of praise; (2) forms of violation of the cooperative principle in the humor found maxim (maxim of quantity, quality maxims, maxims and relation). Three forms of speech in conversational humor generally describe social phenomenon that is happening in society today; (3) Some of the factors that influence the infringement the cooperative principle, based on the data analysis of violations of the cooperative principles, was namely factors of social conditions and humor.